2013
DOI: 10.1111/cas.12279
|View full text |Cite
|
Sign up to set email alerts
|

Antitumor efficacy of CXC motif chemokine ligand 14 in hepatocellular carcinoma in vitro and in vivo

Abstract: C-X-C motif chemokine ligand 14 (CXCL14) is a novel gene that is expressed in many normal cells but is absent from or expressed at very low levels in cancerous tissues such as head and neck squamous cell carcinoma (HNSCC), prostate cancer, and pancre-atic cancer. However, the relationship between CXCL14 and hepa-tocellular carcinoma (HCC) remains unclear. Therefore, the exact function of CXCL14, which may modulate antitumor immune responses in certain cancers, was evaluated. CXCL14 was down-regulated in HCC ti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
40
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 46 publications
(44 citation statements)
references
References 41 publications
4
40
0
Order By: Relevance
“…FCM analysis indicated that the overexpression of CXCL14 in HR29 cells promoted cell cycle arrest in the G 1 stage. The results of the current study were consistent with the results reported by Wang et al (28) in hepatocellular carcinoma cells.…”
Section: Discussionsupporting
confidence: 94%
See 2 more Smart Citations
“…FCM analysis indicated that the overexpression of CXCL14 in HR29 cells promoted cell cycle arrest in the G 1 stage. The results of the current study were consistent with the results reported by Wang et al (28) in hepatocellular carcinoma cells.…”
Section: Discussionsupporting
confidence: 94%
“…Consistent with the results reported by a number of previous tumor-related studies (23)(24)(25)(26)(27)(28), the present study detected that the expression levels of CXCL14 in colorectal carcinoma tissues were significantly lower than those in normal tissues. The current study did contradict the findings of Zeng et al (32), but was consistent with the results of Cao et al (33).…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…Several previous published studies suggested that CXCL14 and CCR6, members of the chemokine family, may serve as potential biomarker and novel molecular Fig. 4 The efficiency of each CCL19-si RNA in HCC cells target in cancer therapy for HCC [9,10]. Chemokines and chemokine receptors not only have significant roles in cancer metastasis and tumorigenesis but also act as anti-tumor agents.…”
Section: Discussionmentioning
confidence: 99%
“…The cycling conditions were as follows: denaturation at 94°C for 5 min, followed by 40 cycles of 95°C for 30 s, 58°C for 30 s, and 72°C for 20 s. All of the experiments were conducted three times, and the average was determined. The 2 −ΔΔCt formula was used to calculate differential gene expression [19]. …”
Section: Methodsmentioning
confidence: 99%